Exploratory Factor Analysis of Beck Depression Inventory (BDI-II) in College Students from Cajamarca - Andy Rick Sánchez-Villena; Eduardo Farfán Cedrón (Interacciones)
Background: The aim of this study was to analyze psychometric properties of Beck Depression Inventory (BDI) in college students from Cajamarca through exploratory factor analysis (EFA). Methods: The sample was conformed by326 students (73.3% female and 26.7% males) whose average age was 19.7 years old (SD=2.28). The beck Depression Inventory (BDI-II) was applied. Results: The initial results showed a single factor explaining 48.16% variance with a reliability of α = .945; however, due to international, national and theoretical background, a second exploratory factor analysis was forced extracting two factors that explained 54.48% variance and a reliabity of = .843 for the first factor and α = .935 for the second on. Validity in relation with other variables shows a correlation between the BDI-II and the Alarcón Happiness Scale (r = - 585, p <.001), Jong Gierveld Loneliness Scale (r = .392, p <. 001) and the Reynolds Depression Scale (r = .708, p <.001). Conclusion: Two factor model fits better than the one factor model; however, the BDI-II could be unidimensional.